2019
DOI: 10.1007/s41999-019-00273-2
|View full text |Cite
|
Sign up to set email alerts
|

EuGMS survey on structures of geriatric rehabilitation across Europe

Abstract: The aim of this study is to provide an overview on structures of geriatric rehabilitation across Europe. Findings We observed major differences among EuGMS member countries with regard to the availability of geriatric rehabilitation and how it was organized. Despite various barriers in most countries, future improvement in geriatric rehabilitation services is anticipated. Message Work now needs to focus on establishing a consensus on what geriatric rehabilitation should look like to further geriatric rehabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 10 publications
0
31
0
4
Order By: Relevance
“…The aim of this systematic literature review and metaanalysis was to present an overview of the nutritional status on admission and its association with functional parameters in geriatric rehabilitation patients. The pooled prevalence (95% CI) for MNA (nine studies) demonstrated that malnutrition and risk of malnutrition were present in 13% (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and 47% (40-54) of the geriatric rehabilitation population, whereas the pooled estimate (95% CI) of BMI (n = 45) was 23.8 kg/m 2 (23.2-24.5). The ranges of the values and heterogeneity were high among the individual studies of the respective pooled estimates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this systematic literature review and metaanalysis was to present an overview of the nutritional status on admission and its association with functional parameters in geriatric rehabilitation patients. The pooled prevalence (95% CI) for MNA (nine studies) demonstrated that malnutrition and risk of malnutrition were present in 13% (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and 47% (40-54) of the geriatric rehabilitation population, whereas the pooled estimate (95% CI) of BMI (n = 45) was 23.8 kg/m 2 (23.2-24.5). The ranges of the values and heterogeneity were high among the individual studies of the respective pooled estimates.…”
Section: Discussionmentioning
confidence: 99%
“…In general, geriatric rehabilitation consists of a structured program, which is in most countries provided by a team of physicians, nurses, physiotherapists, occupational therapists, speech therapists, psychologists, dietitians and social workers [17]. The meta-analysis of Bachmann et al showed effectiveness of inpatient rehabilitation in older patients (≥ 55 years) in a multidisciplinary rehabilitation setting with regard to the recovery of physical function [15].…”
Section: Introductionmentioning
confidence: 99%
“…The preparation stage comprised two Delphi studies, one about the definition and organisation of GR in Europe [3], and one about the structures for GR across Europe [4]. These are reported in detail elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence that the approaches taken to GR differ between European countries [1]. Comparison of how GR is described in curricula for postgraduate education in Germany, the United Kingdom, and The Netherlands revealed agreement about the need for: a multidisciplinary approach, led by a geriatrician, after Comprehensive Geriatric Assessment; a tailored rehabilitation plan with regular evaluation of progress using patient outcome measurements; core competencies in the management of complications including pressure sores, venous thromboembolism, contractures, aspiration pneumonia, and urinary tract infections [2].…”
Section: Introductionmentioning
confidence: 99%